2001
DOI: 10.1046/j.1537-2995.2001.41020172.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of incentives on future blood donation behavior

Abstract: These findings suggest that offering blood credits and (though to a lesser extent) items of limited value could be safe and effective strategies for retaining donors. Although medical tests were found to have broad appeal, studies are needed to identify tests in which donors would be most interested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 21 publications
5
80
2
6
Order By: Relevance
“…The highest response was for future blood credits and medical testing. [18] Another study in Texas also concluded that individuals donate in order to reduce medical risks and that earning future blood credits would be a primary motivator. [19] A study amongst the adults in Mwanza Region, Tanzania also noted a positive attitude towards voluntary blood donation but majority of the people will do so only for an incentive.…”
Section: Discussionmentioning
confidence: 99%
“…The highest response was for future blood credits and medical testing. [18] Another study in Texas also concluded that individuals donate in order to reduce medical risks and that earning future blood credits would be a primary motivator. [19] A study amongst the adults in Mwanza Region, Tanzania also noted a positive attitude towards voluntary blood donation but majority of the people will do so only for an incentive.…”
Section: Discussionmentioning
confidence: 99%
“…The adequacy of blood and blood products depends on the blood donation rate and numbers of blood donors. [1][2][3][4][5][6][7][8] To ensure adequate blood supplies, programs to recruit first-time blood donors to compensate for blood donors who stop donating due to age, illness, donor screening results or other screening tests need to be planned. 9,10 In other words, repeat donors play an important role in ensuring adequate blood supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Is the need for donors and blood recognized? The need for blood and blood donors is critical; less than 5% of the American population donates blood, and the number of units of blood collected has dropped in recent years despite increasing need (SANCHEZ et al 2001;BOULWARE et al 2002;HUPFER, TAYLOR and LETWIN 2005;GLYNN et al 2006). Our data indicate that both donors and non-donors agree that there is a "pressing" need for blood donors and that the need for blood is "great" (Table 3; Fig.…”
Section: Signaling Generosity and Cooperative Intentmentioning
confidence: 71%